Mediating effects of situational motivation in problem solving on risk perception and communicant activeness during COVID-19 mobility restrictions in China - Liu, Jie. (2024)
Mediating effects of situational motivation in problem solving on risk perception and communicant activeness during COVID-19 mobility restrictions in China public) were categorised based on public behaviour. A total of 632 respondents in Beijing were selected via cluster sampling to address the online questionnaire. The survey data were subsequently analysed with Statistical Product and Service Solutions (SPSS) and Structural Equation Modelling (SEM). Based on the analysis outcomes, both the active (48%) and aware (29%) public were the key research groups. The hypotheses tested in this study were duly supported. The empirical outcomes are presented as follows: (i) Risk perception (RP) significantly affected public recognition; (ii) problem recognition (PR) and involvement recognition (IR) positively influenced health information communicant activeness (CA) via situational motivation in problem-solving (SMPS); and (iii) constraint recognition (CR) negatively affected health information communicant activeness (CA) via situational motivation in problem-solving (SMPS). In essence, the active public can serve as activists to address public mobility restriction issues during COVID-19. Public relations primarily aim to mobilise the aware public to become an active one. This empirical work examines the effectiveness of STOPS applied to COVID-19 and incorporates risk perception into a theoretical framework, which explains public response to mobility restrictions. The current outcomes potentially catalyse health information communication strategies and public relations to improve policy communication and public adherence by understanding different public segments' behaviours.